Characteristics and evaluation of potential drug interactions among HIV/AIDS outpatients: a retrospective study at primary health center in a North Lampung regency, Indonesia - Nabila, Novrilia Atika; Karim, Miska Aulia; Akhmad, Atika Dalili (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2025)
People living with HIV/AIDS require lifelong antiretroviral therapy (ART) and frequently experience complications and comorbidities that raise the risk of drug-drug interactions. This study aimed to characterize the patients, describe their medication use, and identify potential drug interactions among HIV/AIDS patients at a primary health center in North Lampung Regency. We performed a retrospective, descriptive review of medical records from January to December 2024. All eligible HIV/AIDS patients (N = 31) were included via total sampling. Drug interaction screening used the Lexicomp® application and Stockley’s Drug Interactions. The results showed that most HIV/AIDS patients were male (74.19%), aged 36–45 years (41.93%), and classified as WHO clinical stage I (38.70%). The first‑line ART regimen TLE (tenofovir + lamivudine + efavirenz) was prescribed to 54.8% of patients. A total of 35 potential interactions were identified: 65.7% were moderate pharmacokinetic, 28.6% minor pharmacokinetic, and 5.7% pharmacodynamic (2.9% major and 2.9% moderate). Moderate pharmacokinetic interactions predominated, underscoring the importance of proactive screening and ongoing medication review by pharmacists to prevent adverse events and optimize therapy in HIV/AIDS care.